Altitude - Jamieson, Leland, 1904-1941; Molt, William (Salt Lake City, UT : Project Gutenberg, 2025)
"Altitude by Leland Jamieson" is an aviation adventure short story written in the early 20th century. The story centers on a free-balloon expert$1 (Bs bid for an altitude record, highlighting the dangers of high-altitude flight, the necessity of precise equipment, and the thin line between mastery and catastrophe. Captain Conway prepares the giant hydrogen balloon Marie IV for a record-breaking ascent, aided by his sober, loyal crewman Kisner and the talkative, unreliable Welkfurn. A critical delay keeps a de-oiled, cold-proof clock from reaching the field in time, and Conway launches with a standard clock that soon freezes. As he climbs into the stratosphere, oxygen dwindles, paralysis creeps over his body, and the stopped clock robs him of his timing. At the peak, near death, he manages to trigger the rip-cord, causing a disastrous deflation; the balloon fails to parachute properly and plummets. Regaining just enough awareness near the ground, he bails out under his own parachute and survives. Rescued by Kisner and a chastened Welkfurn, he later reflects on the razor$1 (Bs edge of his success$1 (Bboth the new record and his life saved by a last-moment escape. (This is an automatically generated summary.)s
Release date is 2025-05-24
Roger Frank and Sue Clark
Keywords: Short stories; Ballooning -- Fiction; Parachuting -- Fiction